EVEN GRACEFUL LABELING OF SOME NEW GRAPHS (International Journal of Engineering and Computer Science, 2017)
In this paper some new even graceful graphs are investigated. We prove that the graph obtained by joining two copies of even cycle Cn with path Pk and the splitting graph of K1,n admits even graceful labelling.